(3GdeNJGQ ef efGbH GdCNjGQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eMeO Hf YeQ Hf GdMSf s)
(3ChdgG (B:s
(3jHOC HJQLeI YHOGdQMef Hf YeQh GdChRGYi s
(3GdehLhO efg GdfUa GdKGfis
(3GfXQ GjVG HQbe(B448 (3hQbe (B782s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs